Effects of 12 Weeks Aerobic Training on Body Composition, Serum Homocysteine and CRP Levels in Obese Women - Farzaneh Taghian; Mehdi Kargarfard; Roya Kelishadi (مجله دانشکده پزشکی اصفهان, 2011)
Background: Epidemiological studies indicate that elevated serum levels of homocysteine and C-reactive protein (CRP) is independently associated with risk of cardiovascular disease. The aim of this study was to determine the effects of 12 weeks aerobic training on levels of serum homocysteine and CRP levels in obese women. Methods: 20 healthy obese female students with similar age and weight were randomly devided in intervention and control groups. The intervention group was trained in an aerobic exercise program for 12 weeks (3 sessions weekly). This program was a treadmill exercise with 50-65 percent maximum heart rate intensity for 30-45 minutes in each session. Weight, body fat percentage, body mass index and waist to hip ratio were measured in the beginning and the end of the study for all of the subjects by using the analysis of body composition. In addition homocysteine and CRP levels in the fasting state were evaluated with ELISA (enzyme–linked immunosorbent assay) method before and after the exercise program. Data were analyzed by the Paired t-test and covariance analysis test. Findings: The mean age in both groups were 25 ± 5 years. The results showed a significant decrease in weight, fat percentage, body mass index, waist to hip ratio parameters and homocysteine and CRP levels in exercise group after 12 week exercise period. At the end of the study we found statistically significant differences in weight, fat percentage, body mass index, waist hip ratio parameters and homocysteine and CRP levels between 2 groups. Conclusion: According to our result, a 12 week regular aerobic exercise program, with moderate-intensity play an important role in weight control in obese individual and decrease their cardiovascular disease risk factors.